The Italian block of the ESCB multi-country model - Elena Angelini; Antonello D'Agostino; Peter McAdam (European Central Bank (ECB), 2006)
This paper documents the structure, estimation and simulation properties of the Italian block of the ESCB-multi-country model (MCM). The model is used regularly as an input into Eurosystem projection exercises and, to a lesser extent, in simulation analysis. The specification of the Italian model follows closely that of the Area-Wide Model (AWM) and indeed the other MCM country blocks (in terms of specification and accounting framework). The MCM is a quarterly estimated structural macroeconomic model that treats the economy in a relatively closed manner. It has a long-run classical equilibrium with a vertical Phillips curve but with some short-run frictions in price/wage setting and factor demands. Consequently, activity is demand-determined in the short-run but supply-determined in the longer run with employment having converged to a level consistent with an exogenously given level of equilibrium unemployment. The precise properties of the model are illustrated using a number of standard variant simulations.
Keywords: C3; C5; E1; E2; 330; Italy; Macro-econometric Modelling; Makroökonometrie; Wirtschaftsprognose; Simulation; Zentralbank; EU-Staaten; Italien